Biomarkers: A Definite Plus in Pneumonia - Hanssa Summah; Jie-Ming Qu (Mediators of Inflammation)
During the past few years, biomarkers have emerged as an indispensible tool in the diagnosis of pneumonia. To find an ideal diagnostic biomarker for pneumonia is not an easy task. Not only should it allow an early diagnosis of the condition, but it should also allow differential diagnosis from other noninfectious conditions. Ongoing research is being done in this field so as to put an array of biomarkers at the disposal of doctors to improve the diagnosis of pneumonia when patients present to them with cough or nonspecific symptoms which could easily be misinterpreted as symptoms of other conditions. Procalcitonin and soluble triggering receptor expressed on myeloid cells-1 have emerged as reliable diagnostic markers in pneumonia, and are better when compared to other markers, namely, C-reactive protein, leukocyte count, and proinflammatory cytokines. Many other biomarkers are being studied for their probable use in diagnosing pneumonia but have yet to prove their benefit.